A Hospital Based Study on Association of Herpes Zoster with Diabetes Mellitus (Med Phoenix, 2022)
IntroductionHerpes zoster (HZ) is a viral infection caused by the varicella zoster virus which presents with both neural and cutaneous manifestations. Diabetes mellitus is an endocrine disorder occurring in people which may result in decreased immunity. Several studies have been done in different parts of the world to look for an association between herpes zoster and diabetes mellitus. This study is done to determine any association between herpes zoster and diabetes mellitus.Materials and MethodsThe study was done on newly diagnosed HZ cases attending the outpatient department of Bir Hospital, Kathmandu. Inclusion criteria include new patients presenting with HZ to the department of dermatology, Bir hospital. Patients who refused to participate in the study, who were below 16years, suffering from psychiatric illness, lactating and pregnant females, and those taking drugs that can alter blood glucose levels were excluded from the study. The random blood sugar of each patient was done and in patients with raised blood sugar, fasting and postprandial blood sugar were done.ResultsAround 20% of herpes zoster patients were diabetics at presentation, mostly in the age group >65 years in both male and female. Undiagnosed diabetes mellitus was common in HZ patients.ConclusionOur study showed a higher incidence of diabetes mellitus in patients with herpes zoster mostly in the age group >65 years. So, elderly patients presenting with herpes zoster should be evaluated for a blood glucose levels.